RAGAM ARTI DAN MAKNA TERHADAP KONTRUKSI BANGUNAN ISTANO BASA PAGARUYUNG - Muhammad Yusuf; Akdila Bulanov (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research examines the meaning and function of construction and carving in Istano Basa Pagaruyung as a representation of Minangkabau culture. Istano Basa Pagaruyung is a symbol of the uniqueness and richness of Minangkabau customs that is manifested in the physical form of buildings, pole structures, carvings, and other elements. This research uses a descriptive analysis approach to understand the philosophical, aesthetic and social values contained in these elements. The results show that each part of Istano Basa Pagaruyung not only has an aesthetic role but also symbolises the customary philosophy and cultural teachings that have been passed down from generation to generation